2014
DOI: 10.1255/ejms.1262
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of New Synthetic Drugs by Ion Mobility Time-of-Flight Mass Spectrometry

Abstract: Characteristic ion mobility mass spectrometry data, reduced mobility, and limits of detection (signal-to-noise ratio = 3) were determined for six synthetic drugs and cocaine by ion mobility time-of-flight mass spectrometry (IM-TOF-MS) with electrospray ionization (ESI) and atmospheric pressure chemical ionization (APCI). The studied synthetic illicit drugs recently appeared on the recreational drug market as designer drugs and were methylone, 4-MEC (4'-methylethcathinone), 3,4-MDPV (3,4-methylenedioxypyrovaler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…Kanu et al and Sysoev et al utilized atmospheric pressure ion mobility time-of-flight mass spectrometry (APIM(tof)MS) in the analysis of emerging psychoactive substances and the drift times, reduced mobility, and detection limits for each substance were determined. [35,36] A 63 Ni-IMS has been also used for the detection and characterization of these arising substances by Armenta et al and Joshi et al [37,38] In this current study, a commercial bench-top 63 Ni-IMS and DART ionization source coupled to the quadrupole time-of-flight mass spectrometer (QTOF-MS) are employed for the purpose of rapid detection and identification of an extended number of NPS.…”
Section: Drug Testing and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Kanu et al and Sysoev et al utilized atmospheric pressure ion mobility time-of-flight mass spectrometry (APIM(tof)MS) in the analysis of emerging psychoactive substances and the drift times, reduced mobility, and detection limits for each substance were determined. [35,36] A 63 Ni-IMS has been also used for the detection and characterization of these arising substances by Armenta et al and Joshi et al [37,38] In this current study, a commercial bench-top 63 Ni-IMS and DART ionization source coupled to the quadrupole time-of-flight mass spectrometer (QTOF-MS) are employed for the purpose of rapid detection and identification of an extended number of NPS.…”
Section: Drug Testing and Analysismentioning
confidence: 99%
“…and Sysoev et al . utilized atmospheric pressure ion mobility time‐of‐flight mass spectrometry (APIM(tof)MS) in the analysis of emerging psychoactive substances and the drift times, reduced mobility, and detection limits for each substance were determined . A 63 Ni‐IMS has been also used for the detection and characterization of these arising substances by Armenta et al .…”
Section: Introductionmentioning
confidence: 99%
“…Especially for drug analysis, IMS proved to be very versatile and was applied for the analysis of classical drugs both in forensic science and forensic toxicology; [96][97][98][99][100][101][102] the analysis of psilocin and psilocybin in mushrooms; 103 the analysis of MDMA, MDEA, methamphetamine, cocaine, and clenbuterol in hair samples; [104][105][106] analysis of volatile drug markers of cocaine, MDMA, and THC in air samples; 107 and the analysis of benzodiazepines. 108 In the last few years, a number of NPS have been successfully analyzed using IMS such as cathinones, [109][110][111][112] tryptamines, 109,110,112 synthetic cannabinoids 8,111,112 and phenethylamines. 111,112 The selectivity of the mobile IMS is limited and some publications reported that analytes with nearly identical chemical structure like the synthetic cannabinoids cannot be distinguished.…”
Section: Currently Mobile Spectroscopic Techniques Like Infrared (Irmentioning
confidence: 99%
“…It is more important for focusing of the ions at atmospheric pressure in ion mobility spectrometry/mass spectrometry (IMS/MS). Such combinations were reported for ion mobility spectrometer/time-of-flight mass spectrometer (IMS/TOF MS), [6][7][8][9] ion mobility spectrometer/quadrupole mass spectrometer (IMS/QMS), 10 and for field asymmetric ion mobility spectrometer/mass spectrometer (FAIMS/MS) 11,12 and for aspiration ion mobility spectrometer/mass spectrometer. 13 For all the combinations, a 90%-99% of the losses occur at inlet of MS.…”
Section: Introductionmentioning
confidence: 99%